PEMBERIAN PENGETAHUAN DAN PRAKTEK PEMBUATAN TEPUNG UWI UNGU SEBAGAI SUMBER ANTIOKSIDAN DI KWT TRI MANUNGGAL DUSUN BEJI KABUPATEN BANTUL YOGYAKARTA - Tamaroh, Siti (Universitas Muhammadiyah Mataram, 2020)
Purple yam is a source of carbohydrates that have potential as a source of natural antioxidants. The use of purple yam is still limited by steaming it and consuming it directly. The purpose of making purple yam flour is to extend its shelf life and make it easier to use. The provision of knowledge and practice is carried out at KWT Tri Manunggal, Beji Kulon , Sendangsari , Pajangan , Bantul , Yogyakarta. Knowledge sharing is carried out through discussion and practice. The results of community service show that the community can understand the importance of using purple uwi as a food ingredient and processed with anthocyanin levels as a natural antioxidant. Processing of purple uwi tubers to flour can extend the shelf life of raw materials and make it easier if they are processed into various processed forms.